Helicobacter pullorum in broiler chickens and the farm environment: a one health approach - Wai, Soe Soe; Abdul Aziz, Saleha; Bitrus, Asinamai Athliamai; Zakaria, Zunita; Abu, Jalila (Veterinary World, 2019)
Aim: This study aimed to investigate the occurrence of Helicobacter pullorum in broiler chickens and their farm environment.